LEUKEMIA – TYPES, CLINICAL APPEARANCES, DIAGNOSIS AND TREATMENT - Azizbek Mo‘minjonov Akmaljon o‘g‘li; Mamatojiyev Shohjahon Abdullajon o‘g‘li; Musayev Hamid Alimardonovich (Web of Journals Publishing, 2024)
Leukemia is a tumor originating from hematopoietic cells that is primarily located in the bone marrow and causes leukemia as a sign of the disease. In the vernacular, it is called leukosis, and in medicine it is called leukosis. Leukemia is an oncological condition – blood cancer. The exact causes of the disease are still unknown to medicine, and there are no preventive measures. Children, women, and adults can get this disease. The disease is registered more often in industrialized cities than in rural areas; men are more affected than women. The disease occurs all over the world – both in developed and underdeveloped countries. Leukemia is one of the urgent problems of modern medicine, but it has not yet been thoroughly solved. According to international statistics, the number of deaths from leukemia has been increasing in recent years. About 1% of all causes of death are people who die from leukemia, and about 6% from malignant tumors, and 50% in children and adolescents. Leukemia is a complex disease and is included in the list of diseases that can be treated in the 21st century. If we look at Uzbekistan, 20 years ago, the methods of effective treatment of leukemia were not yet studied to that extent. Until now, treatment methods have been developed to overcome this disease. In leukemia, abnormal blood cells are produced in the bone marrow. Usually, the disease is characterized by the production of abnormal types of leukocytes, which are responsible for fighting infection. In a white blood cell disease, abnormal cells do not perform the same functions as normal leukocytes. Cancer cells grow and actively divide, interfering with the movement of other blood cells. As a result, there is a decrease in the body’s ability to fight infections, loss of control of bleeding, and difficulty in transporting oxygen. Leukemias include a wide group of diseases that differ in their etiology. In leukemias, blood cells of poor quality can arise from immature hematopoietic cells of the bone marrow, as well as from maturing and mature blood cells. Currently, all neoplastic diseases of blood-forming tissues are called hemoblastoses. According to the nature and location of pathological processes, they are divided into two groups. According to the World Health Organization, in recent years, the number of deaths from leukemia has been increasing across countries.